Electrochemical Modeling of Commercial LiFePO4 and Graphite Electrodes: Kinetic and Transport Properties and Their Temperature Dependence. Issue 13 (1st January 2016) - Mastali, Mehrdad; Farkhondeh, Mohammad; Farhad, Siamak; Fraser, Roydon A.; Fowler, Michael
Abstract : Based on the variable solid-state diffusivity concept, a semi-physical model is developed to simulate the electrochemical performance of commercial LiFePO4 (LFP) and graphite electrodes. Although the developed model is not accurately describing the phase change process within the active material, it is reliable for engineering applications such as battery management, thermal analysis and management, and aging studies. The developed LFP and graphite models extend previous works by validating the models against galvanostatic charge/discharge experiments conducted at various currents (C/5 to 5C) and temperatures (10°C, 23°C, 35°C, and 45°C). The fidelity of the model is confirmed by the satisfactory fit of the model to the experimental data for two different materials over a wide range of operating conditions. Temperature dependency of transport and kinetic properties of LFP and graphite is analyzed, and yields the activation energies of 86 kJ mol −1 and 20 kJ mol −1 for diffusion of intercalated species in LFP and graphite particles, respectively. The activation energies for charge transfer reaction at the surface of LFP and graphite particles are also found to be 9 kJ mol −1 and 20 kJ mol −1, respectively. The estimated kinetic and transport parameters and their temperature dependencies can be reliably used in thermal, electrochemical, or aging modeling of batteries involving these two materials.